Case Report:Pregnancy and birth in a mild phenotype of Alström syndrome - Marozio, Luca; Dassie, Francesca; Bertschy, Gianluca; Canuto, Emilie M.; Milan, Gabriella; Cosma, Stefano; Maffei, Pietro; Benedetto, Chiara (Frontiers in Genetics, 2022)
Background: Alström Syndrome (AS) is an ultra-rare multisystemic progressive disease caused by autosomal recessive variations of the ALMS1 gene (2p13). AS is characterized by double sensory impairment, cardiomyopathy, childhood obesity, extreme insulin resistance, early non-alcoholic fatty liver disease, renal dysfunction, respiratory disease, endocrine and urologic disorders. In female patients hyperandrogenism has been described but fertility issues and conception have not been investigated so far. Case: This case report describes the spontaneous conception, pregnancy and birth by a 27 years-old woman with AS, characterized by a mild phenotype with late onset visual impairment, residual perception of light and hypertension. Before pregnancy menses were regular with increased level of dihydrotestosterone and androstanediol glucuronide on follicular phase, ovaries and endometrium were normal at vaginal ultrasound. A thorough clinical follow-up of maternal and fetal conditions was carried out. A weight gain of 10 kg during pregnancy was recorded and serial blood and urine tests were all within the normal range, except for a mild anemia. The course of pregnancy was uneventful up to 34 weeks gestation when preeclampsia developed with abnormally high level of blood pressure and lower limbs oedema. At 35 weeks plus 3 days of gestation urgent cesarean section was performed and a healthy male weighing 1,950 g was born. Histological examination of the placenta showed partial signs of flow obstruction, limited abruption areas, congested fetal vessels and villi, and a small single infarcted area. Conclusion: The present case demonstrates for the first time that conceiving is possible for patients with ALMS. A particular attention should be observed for the management of AS systemic comorbidities through the course of pregnancy.